Inactivation of waterborne fungal spores by 1-bromo-3-chloro-5, 5-dimethylhydantoin: Kinetics, influencing factors and mechanisms. (July 2021) - Wen, Gang; Tan, Lili; Cao, Ruihua; Wan, Qiqi; Xu, Xiangqian; Wu, Gehui; Wang, Jingyi; Huang, Tinglin
Abstract: Fungal contamination in drinking water source has become a problem worth studying, as waterborne fungi may cause deterioration of water quality and outbreak of diseases. Various disinfection methods have been explored to control fungal spores in drinking water, such as chlor(am)ination, ozonation, chlorine dioxide treatment, but these methods are not appropriate for remote areas, owing to the difficulties in preparation, carriage and storage. In this study, a powdery disinfectant of 1-bromo-3-chloro-5, 5-dimethylhydantoin (BCDMH), which facilitated transportation and preservation, was firstly chosen to inactivate opportunistic pathogens of Aspergillus niger ( A. niger ) and Penicillium polonicum ( P. polonicum ). The results revealed that the inactivation kinetics of fungal spores by BCDMH fitted to Chick-Watson model well, with the inactivation rate constant of 0.011 and 0.034 L mg −1  min −1 for A. niger and P. polonicum, respectively. Acidic condition and high temperature promoted the inactivation by BCDMH. Compared with chlorine, BCDMH showed relative weaker ability on inactivation of fungal spores. However, it was demonstrated that the inactivation efficiency of BCDMH was obviously enhanced by adding halide ions, with 11 or 36 folds for A. niger and 4 or 15 folds for P. polonicum by adding 40 μM Br − or I − . The inactivation mechanisms were detected by flow cytometry and scanning electron microscope. Fungal spores lost their culturability firstly, then membrane integrity was damaged. Meanwhile, the esterase activity and intracellular reactive oxygen species level changed, and finally intracellular adenosine triphosphate released. Graphical abstract: Image 1 Highlights: The inactivation of fungal spores by BCDMH fitted to Chick-Watson model well. Acidic condition and high temperature promoted the inactivation by BCDMH. The addition of halide ions enhanced the inactivation efficiency by BCDMH. Underlying inactivation mechanisms of fungal spores by BCDMH were revealed.